A research program for the socioeconomic impacts of gene editing regulation. Issue 1 (2nd January 2017) - Whelan, Agustina I.; Lema, Martin A.
ABSTRACT: Gene editing technologies are a group of recent innovations in plant breeding using molecular biology, which have in common the capability of introducing a site-directed mutation or deletion in the genome. The first cases of crops improved with these technologies are approaching the market; this has raised an international debate regarding if they should be regulated as genetically modified crops or just as another form of mutagenesis under conventional breeding. This dilemma for policymakers not only entails issues pertaining safety information and legal/regulatory definitions. It also demands borrowing tools developed in the field of social studies of science and technology, as an additional basis for sound decision making.